Regulation and control method and device of composite material, electronic equipment and storage medium

By regulating the chemical activity and geometric dimensions of the filler material, the problem of monotonic strength relationship of inorganic gelling materials is solved, and the strength and fracture properties of the composite material are independently designed, which improves the toughening efficiency and performance of the fiber composite material.

CN119181445AActive Publication Date: 2024-12-24WUHAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411211104.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-24
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The monotonicity of the strength relationship of inorganic cementitious materials makes it difficult for composite materials to achieve independent design of strength properties and fracture properties, limiting the toughening efficiency of fiber composite materials.

Method used

By regulating the chemical activity and geometric dimensions of the filler material, the replacement ratio of the filler material, the filler particle size and the replacement material are determined, and the independent design of the gelling capacity and density are achieved, thereby decoupling the relationship between strength and fracture properties and realizing inorganic glue Two-way regulation of the tough relationship between coagulants.

Benefits of technology

The independent design of the strength and fracture properties of the composite material is achieved, the compressive strength and tensile ductility of the fiber composite material are improved, and the fiber reinforcement and toughening are coordinated to design fiber reinforcement and toughening, which promotes infrastructure safety and material performance optimization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181445A_ABST
    Figure CN119181445A_ABST
Patent Text Reader

Abstract

The invention relates to a composite material regulation and control method and device, electronic equipment and a storage medium, and the method comprises the steps: obtaining the compressive strength and fracture toughness of an initial composite material and the compressive strength and fracture toughness of a target composite material; according to the compressive strength and the fracture toughness of the initial composite material and the compressive strength and the fracture toughness of the target composite material, determining a filling material, a filling particle size of the filling material, a replacement material and a replacement proportion of the replacement material, and preparing the target composite material according to the filling material, the filling particle size of the filling material, the replacement material and the replacement proportion of the replacement material. Therefore, the problem that the strength property and the fracture property of the composite material are difficult to independently design due to the monotonicity of the strength and toughness relationship of the inorganic cementing material is solved, and the independent design of the gelling capacity and the compaction degree is realized by regulating and controlling the chemical activity and the geometric dimension of the filling material; therefore, bidirectional regulation and control of the strength and toughness relationship of the inorganic cementing material are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inorganic non-metallic materials, and in particular to a control method, device, electronic device and storage medium for composite materials. Background Art

[0002] Inorganic cementitious materials are the material category with the largest output in the world. Among them, concrete materials produced with cement as the cementitious system have an annual global output of up to 14 billion cubic meters. They are a basic element in the construction of various types of infrastructure. However, inorganic cementitious materials are mostly brittle and their failure form is sudden fracture. Therefore, on the basis of strength property design, changes in fracture properties must be considered.

[0003] The design of the fracture properties of cementitious materials in related technologies mainly relies on experience. On the basis of determining that the compressive strength meets the technical needs, the fracture toughness is obtained through experiments, and the necessary improvements are made to the material composition according to the change law of the cementitious materials. Taking cement as an example, adjusting the water-cement ratio and the proportion of active ingredients is currently the main means of optimizing the composition of cementitious materials. In most cases, since cement and concrete are mainly used to bear compressive loads in engineering structures, their material design is mostly dominated by compressive strength. Studies have shown that there is a general positive correlation between the compressive strength and fracture toughness of inorganic cementitious materials. Therefore, unidirectional improvement of compressive strength can also play a toughening role to a certain extent. However, due to its own brittle characteristics, this toughening effect is very limited.

[0004] The establishment of composite materials based on inorganic cementitious materials can significantly improve the toughness of infrastructure materials. Based on this, related technologies have developed a series of material systems such as fiber reinforced concrete (FRC), ultra-high performance concrete (UHPC), strain-hardened fiber reinforced cement-based composites (ECC / SHCC), etc. In the design of these materials, generating multiple cracks under load is considered to be one of the important ways to improve the toughness of materials, such as Figure 1 Shown and Figure 2 As shown in the figure, since the brittleness of the cement matrix itself is difficult to avoid, transforming the single crack in the traditional brittle material system into multiple cracks under fiber bridging can greatly improve the material's ability to absorb external energy, thereby playing a significant role in toughening.

[0005] In the above composite material system, in order to promote multi-cracks, the cementitious material matrix must have a fracture toughness KIC as small as possible, so that cracks can quickly expand in a flat form (flat cracking) after they occur, thereby completing crack expansion before the fiber bridging capacity is exhausted. The positive correlation between strength and toughness generally possessed by inorganic cementitious materials leads to an increase in fracture toughness while the compressive strength of the matrix increases, thereby suppressing multi-cracks and limiting the improvement in toughness of the composite material. Therefore, even under the toughening effect of fibers, most composite materials still show a phenomenon in which the toughening efficiency decreases with increasing compressive strength.

[0006] In summary, one of the fundamental ways to improve the toughening efficiency of high-strength fiber composites is to decouple the strength-toughness relationship of its cementitious material matrix to achieve independent design of the matrix compressive strength and fracture toughness, and when any one of the variables is determined, the value range of the other variable can be adjusted through material optimization design. However, there are no corresponding technical means in the relevant technology, and it is difficult to solve the technical bottleneck of strengthening and toughening fiber composites. Summary of the invention

[0007] The present application provides a method, device, electronic device and storage medium for regulating composite materials to solve the problem that due to the monotonicity of the strength-toughness relationship of inorganic gelling materials, it is difficult to independently design the strength properties and fracture properties of composite materials. By regulating the chemical activity and geometric dimensions of the filling material, the gelling ability and density can be independently designed, thereby realizing two-way regulation of the strength-toughness relationship of the inorganic gelling material.

[0008] The first aspect of the present application provides a method for controlling a composite material, comprising the following steps:

[0009] Obtaining the compressive strength and fracture toughness of the initial composite material, and the compressive strength and fracture toughness of the target composite material;

[0010] Determining a filler, a filling particle size of the filler, a replacement material, and a replacement ratio of the replacement material according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material;

[0011] The target composite material is prepared according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material.

[0012] Optionally, in some embodiments, determining the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material includes:

[0013] If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a first preset threshold, and the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is greater than a second preset threshold, at least one fine particle inert material is determined as a filler, at least one of a cementitious material, water and a coarse particle material in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a first ratio;

[0014] If the absolute value of the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is less than a third preset threshold, and the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fourth preset threshold, wherein the fourth preset threshold is greater than the third preset threshold, then at least one fine particle inert material and / or at least one active material is determined as a filler, at least one of a cementitious material, water and coarse particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a second ratio;

[0015] If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fifth preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a sixth preset threshold, wherein the fifth preset threshold is greater than the sixth preset threshold, then at least one fine particle inert material and / or at least one active material is determined as a filler, at least one of water and coarse particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a third ratio;

[0016] If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a seventh preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than an eighth preset threshold, wherein the eighth preset threshold is greater than the seventh preset threshold, then at least one coarse particle inert material and / or at least one active material is determined as a filler, at least one of a cementitious material, water and fine particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a fourth ratio;

[0017] If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a ninth preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a tenth preset threshold, at least one active material is determined as a filler, at least one of the gelling material, water and fine particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a fifth ratio.

[0018] Optionally, in some embodiments, the cementitious material is at least one of ordinary Portland cement, sulphoaluminate cement, aluminate cement, magnesium-based cement, carbonate cementitious material, alkali-activated cementitious material, and building gypsum.

[0019] Optionally, in some embodiments, before obtaining the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, the method further comprises:

[0020] Obtain target compressive strength;

[0021] Determining a basic ratio of the initial composite material according to the target compressive strength, and preparing the initial composite material based on the basic ratio;

[0022] The initial composite material is tested to obtain the fracture toughness and actual apparent packing density of the initial composite material, and the particle packing density and particle gap volume of the initial composite material are determined using a preset calculation model.

[0023] Optionally, in some embodiments, after the target composite material is prepared according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material, the method further includes:

[0024] Testing the target composite material to obtain actual compressive strength and actual fracture toughness of the target composite material;

[0025] Determining whether the actual compressive strength is within a preset strength range, and whether the actual fracture toughness is within a preset toughness range;

[0026] If the actual compressive strength is not within the preset strength range, or the actual compressive strength is not within the preset toughness range, the optimized ratio of the target composite material is determined based on the compressive strength and fracture toughness of the target composite material and the actual compressive strength and actual fracture toughness of the target composite material, and the optimized target composite material is prepared based on the optimized ratio.

[0027] A second aspect of the present application provides a control device for a composite material, comprising:

[0028] An acquisition module, used for acquiring the compressive strength and fracture toughness of the initial composite material, and the compressive strength and fracture toughness of the target composite material;

[0029] A determination module, configured to determine a filler, a filling particle size of the filler, a replacement material, and a replacement ratio of the replacement material according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material;

[0030] A preparation module is used to prepare the target composite material according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material.

[0031] Optionally, in some embodiments, the determining module includes:

[0032] a first determining unit, configured to determine at least one fine-grained inert material as a filler, determine at least one of a cementitious material, water and a coarse-grained material in the initial composite material as a replacement material, and determine a replacement ratio of the replacement material to be a first ratio when a difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a first preset threshold value, and a difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is greater than a second preset threshold value;

[0033] a second determining unit, for determining, when an absolute value of a difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is less than a third preset threshold value, and a difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fourth preset threshold value, wherein the fourth preset threshold value is greater than the third preset threshold value, to determine at least one fine particle inert material and / or at least one active material as a filler, to determine at least one of a cementitious material, water and coarse particles in the initial composite material as a replacement material, and to determine a replacement ratio of the replacement material to be a second ratio;

[0034] a third determining unit, for determining, when a difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fifth preset threshold, and a difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a sixth preset threshold, wherein the fifth preset threshold is greater than the sixth preset threshold, at least one fine particle inert material and / or at least one active material as a filler, at least one of water and coarse particles in the initial composite material as a replacement material, and a replacement ratio of the replacement material to be a third ratio;

[0035] a fourth determining unit, for determining, when the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a seventh preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than an eighth preset threshold, wherein the eighth preset threshold is greater than the seventh preset threshold, at least one coarse particle inert material and / or at least one active material as a filler, determining at least one of a cementitious material, water and fine particles in the initial composite material as a replacement material, and determining the replacement ratio of the replacement material to be a fourth ratio;

[0036] a fifth determination unit, for determining at least one active material as a filler, determining at least one of the cementitious material, water and fine particles in the initial composite material as a replacement material, and determining the replacement ratio of the replacement material to be a fifth ratio when the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a ninth preset threshold value, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a tenth preset threshold value.

[0037] Optionally, in some embodiments, the cementitious material is at least one of ordinary Portland cement, sulphoaluminate cement, aluminate cement, magnesium-based cement, carbonate cementitious material, alkali-activated cementitious material, and building gypsum.

[0038] Optionally, in some embodiments, before obtaining the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, the obtaining module includes:

[0039] An acquisition unit, used for acquiring a target compressive strength;

[0040] A preparation unit, configured to determine a basic ratio of the initial composite material according to the target compressive strength, and prepare the initial composite material based on the basic ratio;

[0041] The first testing unit is used to test the initial composite material to obtain the fracture toughness and actual apparent packing density of the initial composite material, and to determine the particle packing density and particle gap volume of the initial composite material using a preset calculation model.

[0042] Optionally, in some embodiments, after the target composite material is prepared according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material, the preparation module further includes:

[0043] A second testing unit is used to test the target composite material to obtain the actual compressive strength and actual fracture toughness of the target composite material;

[0044] A judging unit, used to judge whether the actual compressive strength is within a preset strength range, and whether the actual fracture toughness is within a preset toughness range;

[0045] An optimization unit is used to determine an optimized ratio of the target composite material based on the compressive strength and fracture toughness of the target composite material and the actual compressive strength and actual fracture toughness of the target composite material when the actual compressive strength is not within a preset strength range or the actual compressive strength is not within a preset toughness range, and to prepare an optimized target composite material based on the optimized ratio.

[0046] A third aspect of the present application provides an electronic device, comprising: a memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor executes the program to implement the method for controlling the composite material as described in the above embodiment.

[0047] A fourth aspect of the present application provides a computer-readable storage medium having a computer program stored thereon, which is executed by a processor to implement the method for controlling the composite material as described in the above embodiment.

[0048] Thus, by obtaining the compressive strength and fracture toughness of the initial composite material, the compressive strength and fracture toughness of the target composite material, and determining the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, and preparing the target composite material according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material. Thus, the problem that the composite material is difficult to independently design the strength properties and fracture properties due to the monotonicity of the strength-toughness relationship of the inorganic gelling material is solved, and the independent design of the gelling capacity and the density is achieved by regulating the chemical activity and geometric size of the filler, thereby realizing the two-way regulation of the strength-toughness relationship of the inorganic gelling material.

[0049] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0051] Figure 1 Schematic diagram of multi-crack cracking characteristics of fiber composite materials;

[0052] Figure 2 Schematic diagram of strain hardening characteristics of fiber composite materials under uniaxial tension multi-crack cracking;

[0053] Figure 3 A flow chart of a method for controlling a composite material provided according to an embodiment of the present application;

[0054] Figure 4 A schematic diagram of a fracture toughness testing method provided according to an embodiment of the present application;

[0055] Figure 5 A schematic diagram of the filling effect of the gelling material provided according to one embodiment of the present application;

[0056] Figure 6 A schematic diagram of a strong-toughness relationship control range provided according to an embodiment of the present application;

[0057] Figure 7 A block diagram of a control device for a composite material provided according to an embodiment of the present application;

[0058] Figure 8 It is a schematic diagram of the structure of an electronic device provided according to an embodiment of the present application. DETAILED DESCRIPTION

[0059] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0060] The following describes the control method, device, electronic device and storage medium of the composite material of the embodiment of the present application with reference to the accompanying drawings. In view of the problem mentioned in the above background technology that it is difficult for composite materials to achieve independent design of strength properties and fracture properties due to the monotonicity of the strength-toughness relationship of inorganic gelling materials, the present application provides a control method for composite materials, in which the compressive strength and fracture toughness of the initial composite material, the compressive strength and fracture toughness of the target composite material are obtained, and the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material are determined according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, and the target composite material is prepared according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material. Thus, the problem that it is difficult for composite materials to achieve independent design of strength properties and fracture properties due to the monotonicity of the strength-toughness relationship of inorganic gelling materials is solved, and the independent design of gelling ability and density is achieved by regulating the chemical activity and geometric size of the filler, thereby achieving two-way control of the strength-toughness relationship of inorganic gelling materials.

[0061] Specifically, Figure 1 A schematic flow chart of a method for controlling a composite material provided in an embodiment of the present application.

[0062] like Figure 1 As shown, the control method of the composite material comprises the following steps:

[0063] In step S101, the compressive strength and fracture toughness of the initial composite material, and the compressive strength and fracture toughness of the target composite material are obtained.

[0064] It should be noted that the composite material in the embodiment of the present application is based on a gelling material.

[0065] Optionally, in some embodiments, before obtaining the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, the process includes: obtaining the target compressive strength; determining a basic ratio of the initial composite material according to the target compressive strength, and preparing the initial composite material based on the basic ratio; testing the initial composite material to obtain the fracture toughness and actual apparent packing density of the initial composite material, and determining the particle packing density and particle gap volume of the initial composite material using a preset calculation model.

[0066] The preset calculation model may be a De Larrard model.

[0067] It is understandable that, within the framework of linear elastic fracture mechanics, the brittle characteristics of inorganic cementitious materials can be quantitatively characterized by fracture toughness K. In the type I fracture mode, when the stress intensity factor reaches the critical value KIC, the crack will expand unstably. Similar to the strength parameters of the material, fracture toughness is an inherent property of the material and does not change with changes in external load conditions.

[0068] Specifically, the embodiment of the present application can preliminarily formulate a basic ratio of the initial composite material according to the target compressive strength; through a three-point bending test, the mode I fracture toughness KIC of the basic ratio is measured, such as Figure 4 As shown; the De Larrard model is used to calculate the particle packing density and particle gap volume of the basic ratio, and the actual apparent packing density of the cementitious material is measured by the wet method, where the particle gap volume is the upper limit of the fine particle filling volume ratio.

[0069] In step S102, fillers, filling particle sizes of the fillers, replacement materials and replacement ratios of the replacement materials are determined according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material.

[0070] Optionally, in some embodiments, Figure 5As shown, the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material are determined according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, including: if the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a first preset threshold, and the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is greater than a second preset threshold, then at least one fine particle inert material is determined as the filler, at least one of the cementitious material, water and coarse particle material in the initial composite material is determined as the replacement material, and the replacement ratio of the replacement material is determined to be a first ratio; if the initial If the absolute value of the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is less than the third preset threshold, and the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than the fourth preset threshold, wherein the fourth preset threshold is greater than the third preset threshold, then at least one fine particle inert material and / or at least one active material is determined as a filler, at least one of the gelling material, water and coarse particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be the second ratio; if the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than the fifth preset threshold, and the target composite material The difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a sixth preset threshold, wherein the fifth preset threshold is greater than the sixth preset threshold, then at least one fine particle inert material and / or at least one active material is determined as a filler, at least one of water and coarse particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a third ratio; if the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a seventh preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than an eighth preset threshold, wherein the eighth preset threshold is greater than the seventh preset threshold, then determine At least one coarse-grained inert material and / or at least one active material is used as a filler, at least one of the cementitious material, water and fine particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a fourth ratio; if the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a ninth preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a tenth preset threshold, then at least one active material is determined as a filler, at least one of the cementitious material, water and fine particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a fifth ratio.

[0071] Among them, the first preset threshold to the tenth preset threshold can be pre-set by the user, can be obtained through a limited number of experiments, or can be obtained through a limited number of computer simulations, and are not specifically limited here; the cementitious material in the embodiment of the present application includes: at least one of ordinary Portland cement, sulfoaluminate cement, aluminate cement, magnesium-based cement, carbonate cementitious material, alkali-activated cementitious material, and building gypsum.

[0072] It is understandable that the compressive strength of cementitious materials depends on their density and gelling capacity, while their tensile strength mainly depends on the maximum defect size and fracture toughness, which respectively determine the initial cracking cross-section of the material and the ability of cracks to resist unstable expansion after cracking. Among them, fracture toughness mainly depends on the gelling capacity of the material. Therefore, by regulating the particle filling effect, the gelling capacity can be unchanged or changed to a smaller extent while changing the density, thereby achieving the technical goal of decoupling compressive strength and fracture toughness.

[0073] Based on the above scientific basis, the embodiments of the present application can achieve the decoupling of the strength-toughness relationship of inorganic gelling materials and the two-way design of strength and fracture properties. With the inorganic gelling matrix as the original material, by regulating the gelling activity, geometric size and volume content of the filler, the technical effect of improving the density of the gelling material but keeping the gelling ability unchanged; or reducing the gelling ability but keeping the density unchanged or improving is achieved, thereby achieving the technical goal of improving the compressive strength of the gelling material but keeping the fracture toughness unchanged; or reducing the fracture toughness but keeping the compressive strength unchanged or improving. Under certain design requirements, the compressive strength of the gelling material can be greatly improved, but the fracture toughness is unchanged or slightly improved; or the fracture toughness is greatly improved, but the compressive strength is unchanged or slightly improved, so that the change law of the compressive strength and fracture toughness of the gelling material presents reverse or asynchronous characteristics.

[0074] It should be noted that the fillers in the embodiments of the present application are divided into two categories: inert and active. Inert fillers include, but are not limited to, one or more of quartz powder, waste stone powder, limestone powder, and biochar fine particles. Active fillers are powders with volcanic ash reaction activity, including, but not limited to, one or more of fly ash, slag, silica fume, and metakaolin. The fillers are micron-nanometer particles with a maximum particle size range of 15μm to 350μm. The filling effect is that the inorganic granular material is used as a filler, and is mixed with the above-mentioned inorganic gelling material according to the type, activity, particle size and proportion designed in the embodiments of the present application.

[0075] Specifically, if the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a first preset threshold, and the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is greater than a second preset threshold, then the regulation requirements of the composite material of the embodiment of the present application are: constant or improved compressive strength, reduced fracture toughness. At this time, fine-grained inert fillers can be used to replace part of the cementitious material, water and coarse particles. One or more of the fillers, wherein the particle size of the filler is less than 15 μm, and the replacement ratio is one of 0-5%, 5-15%, 15-25%, and 25-35%. In the actual implementation process, the particle size of the filler and the replacement ratio of the replacement material are determined by the actual particle size of the particles, the type of cementitious material, the ratio of the initial composite material and the actual filling effect.

[0076] If the absolute value of the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is less than the third preset threshold, and the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than the fourth preset threshold, wherein the fourth preset threshold is greater than the third preset threshold, then it represents that the control requirements of the composite material of the embodiment of the present application are: constant fracture toughness and improved compressive strength. At this time, one or more of fine-grained inert fillers and active fillers can be used to replace part of one or more of cementitious materials, water and coarse particles by equal volume, wherein the particle size of the filler is less than 15 μm, and the replacement ratio is one of 0-5%, 5-15%, 15-25%, 25-35%, 35-45%, 45-55%, and 55-65%. In the actual implementation process, the particle size of the filler and the replacement ratio of the replacement material are determined by the actual particle size of the particles, the type of cementitious material, the ratio of the initial composite material, the actual filling effect and the compressive strength of the target composite material.

[0077] If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than the fifth preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than the sixth preset threshold, wherein the fifth preset threshold is greater than the sixth preset threshold, then it represents that the control requirements of the composite material of the embodiment of the present application are: a small increase in fracture toughness and a large increase in compressive strength. At this time, one or more of fine-grained inert fillers and active fillers can be used to replace part of the water and one or more of the coarse particles by equal volume, wherein the particle size of the filler is one of less than 15 μm, less than 30 μm, and less than 45 μm, and the replacement ratio is one of 0-5%, 5-15%, 15-25%, 25-35%, 35-45%, 45-55%, and 55-65%. In the actual implementation process, the particle size of the filler and the replacement ratio of the replacement material are determined by the actual particle size of the particles, the type of cementitious material, the ratio of the initial composite material, the actual filling effect, and the compressive strength of the target composite material.

[0078] If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than the seventh preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than the eighth preset threshold, wherein the eighth preset threshold is greater than the seventh preset threshold, then it represents that the control requirements of the composite material of the embodiment of the present application are: the compressive strength is constant or slightly improved, and the fracture toughness is greatly improved. At this time, one or more of coarse-grained inert fillers and active fillers can be used to replace part of the one or more of cementitious materials, water and fine particles by equal volume, wherein the median D50 of the particle size of the coarse-grained filler is one of 30μm or more, 45μm or more, 75μm or more, and 125μm or more, and the replacement ratio is one of 0-5%, 5-15%, 15-25%, and 25-35%. In the actual implementation process, the particle size of the filler and the replacement ratio of the replacement material are determined by the actual particle size of the particles, the type of cementitious material, the ratio of the initial composite material and the actual filling effect.

[0079] If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than the ninth preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than the tenth preset threshold, then the regulation demand of the composite material of the embodiment of the present application is: the compressive strength and the fracture toughness are improved simultaneously. At this time, active fillers can be used to replace part of the cementitious material, water and fine particles by equal volume. The particle size of the active filler is one of less than 15 μm, less than 30 μm, and less than 45 μm, and the replacement ratio is one of 0-5%, 5-15%, 15-25%, 25-35%, 35-45%, 45-55%, 55-65%, and 65-75%. In the actual implementation process, the particle size of the filler and the replacement ratio of the replacement material are determined by the actual particle size of the particles, the type of cementitious material, the ratio of the initial composite material, the actual filling effect and the compressive strength of the target composite material.

[0080] In step S103, a target composite material is prepared according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material.

[0081] Specifically, the embodiments of the present application can prepare and cure the target composite material to the designed age according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material.

[0082] Therefore, the embodiments of the present application achieve independent design of gelling capacity and compactness by regulating the chemical activity and geometric size of the filling material, thereby achieving the technical goal of bidirectional regulation (i.e., positive correlation or negative correlation) of the strength-toughness relationship of the inorganic gelling material, such as Figure 6 shown.

[0083] Optionally, in some embodiments, after preparing the target composite material according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material, it also includes: testing the target composite material to obtain the actual compressive strength and actual fracture toughness of the target composite material; judging whether the actual compressive strength is in a preset strength range, and whether the actual fracture toughness is in a preset toughness range; if the actual compressive strength is not in the preset strength range, or the actual compressive strength is not in the preset toughness range, then determining the optimal ratio of the target composite material based on the compressive strength and fracture toughness of the target composite material and the actual compressive strength and actual fracture toughness of the target composite material, and preparing the optimized target composite material based on the optimized ratio.

[0084] The preset strength range and the preset toughness range may be preset by a user, may be obtained through a limited number of experiments, or may be obtained through a limited number of computer simulations, which are not specifically limited here.

[0085] Specifically, after obtaining the target composite material, the embodiment of the present application can test the target composite material to measure the compressive strength and fracture toughness, and fine-tune the proportion of the target composite material according to the measured compressive strength and fracture toughness to obtain an optimized target composite material.

[0086] It should be noted that the control method of the composite material of the embodiment of the present application can be used for the matrix design in the fiber composite material, and form a composite material with high tensile strength and multi-crack opening with the fiber, wherein the fiber is one or more of polyethylene, polyvinyl alcohol, and polypropylene.

[0087] In order to enable relevant technical personnel in the field to further understand the control method of the composite material of the embodiment of the present application, it is described in detail below in conjunction with specific embodiments.

[0088] Embodiment 1:

[0089] The regulation requirements of the embodiments of the present application in the slag cement system are: the compressive strength remains unchanged and the fracture toughness is reduced.

[0090] (1) The initial composite material is slag cement, and the volume content of each component is: 35% silicate cement, 25% slag, and 40% water. After being mixed evenly according to the process specified in ASTMC109, it is cast into 50mm cubes and type I fracture toughness test samples in accordance with ASTM E399. After standard curing for 28 days, the compressive strength is measured to be 68.7MPa and the fracture toughness is 0.4618MPa·m0.5. Based on this basic ratio, an improved ratio with unchanged compressive strength and reduced fracture toughness is designed.

[0091] (2) According to the control method of the composite material of the embodiment of the present application, the inert filler fine quartz powder is used to replace the slag in the cementitious component by equal volume, and the mixing and pouring are completed according to the above process. After curing for 28 days under the same conditions, the compressive strength is measured to be 68.5MPa and the fracture toughness is 0.2611MPa·m0.5. Compared with the basic ratio, the compressive strength of the modified composite material ratio fluctuates within 1%, but the fracture toughness is reduced by 43.5%.

[0092] Embodiment 2:

[0093] The regulation requirements of the embodiments of the present application in the gypsum cementitious system are: the fracture toughness remains unchanged and the compressive strength is improved.

[0094] (1) The initial composite material is a building plaster and a quartz powder filler, and the volume content of each component is: 35% building plaster, 5% quartz powder, and 60% water. It is stirred and poured according to the process in Example 1, and cured for 24 hours. The measured compressive strength is 4.26MPa and the fracture toughness is 0.1111MPa·m0.5. Based on this basic ratio, an improved ratio is designed with unchanged fracture toughness and improved compressive strength.

[0095] (2) The same inert filler fine quartz powder as in Example 1 is used to partially replace water, and the goal of inert filling but unchanged gelling ability is achieved by filling the pores occupied by water that does not participate in the hydration reaction of gypsum in the original system. The revised volume ratio is: 35% building gypsum, 20% quartz powder, and 45% water. Stirring and pouring are completed according to the above process, and curing is carried out under the same conditions for 24 hours. The compressive strength is measured to be 7.80MPa and the fracture toughness is 0.1123MPa·m0.5. Compared with the basic ratio, the fracture toughness of the revised composite material ratio fluctuates by about 1%, but the compressive strength is increased by 83.1%.

[0096] Embodiment 3:

[0097] The regulation requirements of the embodiments of the present application in the slag cement system are: reducing the compressive strength and improving the fracture toughness.

[0098] (1) The initial composite material is slag cement, and the volume content of each component is: 35% silicate cement, 20% slag, and 45% water. It is stirred and poured according to the process in Example 1, and cured for 28 days. The measured compressive strength is 85.2 MPa and the fracture toughness is 0.3958 MPa·m0.5. Based on this basic ratio, an improved ratio is designed with reduced or unchanged compressive strength and improved fracture toughness.

[0099] (2) Using coarse quartz powder as an inert filler, the slag in the cementitious component was replaced by an equal volume, and the mixing and pouring were completed according to the above process. After curing for 28 days under the same conditions, the compressive strength was measured to be 60.3MPa and the fracture toughness was 0.5175MPa·m0.5. Compared with the basic ratio, the compressive strength of the modified composite material ratio decreased by 29.2%, and the fracture toughness increased by 30.7%.

[0100] Embodiment 4:

[0101] The regulation requirements of the embodiments of the present application in the silicate cement system are: increasing the compressive strength and decreasing the fracture toughness.

[0102] (1) The initial composite material is silicate cement, and the volume content of each component is: silicate cement 35%, quartz powder 15%, water 50%, stirring and pouring according to the process in Example 1, curing for 28 days, and the measured compressive strength is 62.6MPa, and the fracture toughness is 0.3177MPa·m0.5. Based on this basic ratio, an improved ratio with increased compressive strength and reduced fracture toughness is designed.

[0103] (2) Use inert filler fine quartz powder to replace the water in the cementitious component by equal volume. The revised volume ratio is: 35% silicate cement, 25% quartz powder, and 40% water. Mixing and pouring are completed according to the above process. After curing for 28 days under the same conditions, the compressive strength is measured to be 68.5MPa and the fracture toughness is 0.2611MPa·m0.5. Compared with the basic ratio, the compressive strength of the revised composite material ratio is increased by 9.4%, but the fracture toughness is reduced by 17.8%.

[0104] In summary, the embodiments of the present application change the inherent monotonicity of the strength-toughness relationship of traditional inorganic cementitious materials, and separate the means of regulating the microstructure density and the cementitious ability of the material by designing cementitious material components containing fillers of different properties, thereby realizing the independent design of the strength properties and the fracture properties. The control method of the composite material of the embodiments of the present application guides the optimal design of the matrix of the fiber composite material, and promotes that the tensile strength and multi-crack cracking properties are also improved while the compressive strength is improved, thereby realizing the coordinated design of the reinforcement and toughening of the fiber composite material, which not only serves the matrix design of high-performance fiber composite materials, but also can guide the preparation of new fillers and the performance customization and optimization design of building materials, and has a certain promoting effect on the improvement of infrastructure safety and the high-value resource utilization of various solid wastes in building materials.

[0105] According to the control method of the composite material proposed in the embodiment of the present application, the compressive strength and fracture toughness of the initial composite material, the compressive strength and fracture toughness of the target composite material are obtained, and the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material are determined according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, and the target composite material is prepared according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material. Thus, the problem that the composite material is difficult to independently design the strength properties and fracture properties due to the monotonicity of the strength-toughness relationship of the inorganic gelling material is solved, and the independent design of the gelling capacity and the degree of density is achieved by regulating the chemical activity and geometric size of the filler, thereby realizing the two-way control of the strength-toughness relationship of the inorganic gelling material.

[0106] Next, the control device of the composite material proposed in the embodiment of the present application is described with reference to the accompanying drawings.

[0107] Figure 7 It is a block diagram of a control device for a composite material according to an embodiment of the present application.

[0108] like Figure 7 As shown, the control device 10 of the composite material includes: an acquisition module 100 , a determination module 200 and a preparation module 300 .

[0109] The acquisition module 100 is used to acquire the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material.

[0110] The determination module 200 is used to determine the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material.

[0111] The preparation module 300 is used to prepare a target composite material according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material.

[0112] Optionally, in some embodiments, the determination module 200 includes: a first determination unit, a second determination unit, a third determination unit, a fourth determination unit and a fifth determination unit.

[0113] Among them, the first determination unit is used to determine at least one fine-particle inert material as a filler, determine at least one of the cementitious material, water and coarse-particle material in the initial composite material as a replacement material, and determine the replacement ratio of the replacement material to be a first ratio when the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a first preset threshold, and the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is greater than a second preset threshold.

[0114] The second determination unit is used to determine at least one fine-particle inert material and / or at least one active material as a filler, determine at least one of a cementitious material, water and coarse particles in the initial composite material as a replacement material, and determine the replacement ratio of the replacement material to be a second ratio when the absolute value of the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is less than a third preset threshold and the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fourth preset threshold, wherein the fourth preset threshold is greater than the third preset threshold.

[0115] The third determination unit is used to determine at least one fine particle inert material and / or at least one active material as a filler, determine at least one of water and coarse particles in the initial composite material as a replacement material, and determine the replacement ratio of the replacement material to be a third ratio when the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fifth preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a sixth preset threshold, wherein the fifth preset threshold is greater than the sixth preset threshold.

[0116] The fourth determination unit is used to determine at least one coarse-grained inert material and / or at least one active material as a filler, determine at least one of the cementitious material, water and fine particles in the initial composite material as a replacement material, and determine the replacement ratio of the replacement material to be a fourth ratio when the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a seventh preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than an eighth preset threshold, wherein the eighth preset threshold is greater than the seventh preset threshold.

[0117] a fifth determination unit, for determining at least one active material as a filler, determining at least one of a cementitious material, water and fine particles in the initial composite material as a replacement material, and determining a replacement ratio of the replacement material to be a fifth ratio when the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a ninth preset threshold value, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a tenth preset threshold value.

[0118] Optionally, in some embodiments, the cementitious material is at least one of ordinary Portland cement, sulphoaluminate cement, aluminate cement, magnesium-based cement, carbonate cementitious material, alkali-activated cementitious material, and building gypsum.

[0119] Optionally, in some embodiments, before obtaining the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, the obtaining module 100 includes: an obtaining unit, a preparation unit and a first testing unit.

[0120] The acquisition unit is used to acquire the target compressive strength.

[0121] The preparation unit is used to determine the basic ratio of the initial composite material according to the target compressive strength, and prepare the initial composite material based on the basic ratio.

[0122] The first testing unit is used to test the initial composite material to obtain the fracture toughness and actual apparent packing density of the initial composite material, and to determine the particle packing density and particle gap volume of the initial composite material using a preset calculation model.

[0123] Optionally, in some embodiments, after preparing the target composite material according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material, the preparation module 300 further includes: a second testing unit, a judgment unit and an optimization unit.

[0124] The second testing unit is used to test the target composite material to obtain the actual compressive strength and actual fracture toughness of the target composite material.

[0125] The judgment unit is used to judge whether the actual compressive strength is within a preset strength range, and whether the actual fracture toughness is within a preset toughness range.

[0126] The optimization unit is used to determine the optimal ratio of the target composite material based on the compressive strength and fracture toughness of the target composite material and the actual compressive strength and actual fracture toughness of the target composite material when the actual compressive strength is not within the preset strength range or the actual compressive strength is not within the preset toughness range, and to prepare the optimized target composite material based on the optimized ratio.

[0127] It should be noted that the above explanations and descriptions of the embodiment of the control method for composite materials are also applicable to the control device for composite materials of this embodiment, and will not be repeated here.

[0128] According to the control device of the composite material proposed in the embodiment of the present application, by obtaining the compressive strength and fracture toughness of the initial composite material, the compressive strength and fracture toughness of the target composite material, and determining the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, and preparing the target composite material according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material. Thus, the problem that the composite material is difficult to independently design the strength properties and fracture properties due to the monotonicity of the strength-toughness relationship of the inorganic gelling material is solved, and the independent design of the gelling capacity and the degree of density is achieved by regulating the chemical activity and geometric size of the filler, thereby realizing the two-way regulation of the strength-toughness relationship of the inorganic gelling material.

[0129] Figure 8 A schematic diagram of the structure of an electronic device provided in an embodiment of the present application. The electronic device may include:

[0130] A memory 801 , a processor 802 , and a computer program stored in the memory 801 and executable on the processor 802 .

[0131] When the processor 802 executes the program, the control method of the composite material provided in the above embodiment is implemented.

[0132] Furthermore, the electronic device further comprises:

[0133] The communication interface 803 is used for communication between the memory 801 and the processor 802 .

[0134] The memory 801 is used to store computer programs that can be executed on the processor 802 .

[0135] The memory 801 may include a high-speed RAM (Random Access Memory) memory, and may also include a non-volatile memory, such as at least one disk memory.

[0136] If the memory 801, the processor 802 and the communication interface 803 are implemented independently, the communication interface 803, the memory 801 and the processor 802 can be connected to each other through a bus and communicate with each other. The bus can be an ISA (Industry Standard Architecture) bus, a PCI (Peripheral Component Interconnect) bus or an EISA (Extended Industry Standard Architecture) bus, etc. The bus can be divided into an address bus, a data bus, a control bus, etc. For ease of representation, Figure 8 Only one thick line is used in the diagram, but this does not mean that there is only one bus or only one type of bus.

[0137] Optionally, in a specific implementation, if the memory 801, the processor 802 and the communication interface 803 are integrated on a chip, the memory 801, the processor 802 and the communication interface 803 can communicate with each other through an internal interface.

[0138] The processor 802 may be a CPU (Central Processing Unit), or an ASIC (Application Specific Integrated Circuit), or one or more integrated circuits configured to implement the embodiments of the present application.

[0139] The embodiment of the present application further provides a computer-readable storage medium having a computer program stored thereon, which, when executed by a processor, implements the above-mentioned method for controlling the composite material.

[0140] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms are not necessarily directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or N embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0141] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, "N" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0142] Any process or method description in a flowchart or otherwise described herein may be understood to represent a module, fragment or portion of code comprising one or more executable instructions for implementing the steps of a custom logical function or process, and the scope of the preferred embodiments of the present application includes alternative implementations in which functions may not be performed in the order shown or discussed, including performing functions in a substantially simultaneous manner or in reverse order depending on the functions involved, which should be understood by technicians in the technical field to which the embodiments of the present application belong.

[0143] It should be understood that the various parts of the present application can be implemented by hardware, software, firmware or a combination thereof. In the above-mentioned embodiment, the N steps or methods can be implemented by software or firmware stored in a memory and executed by a suitable instruction execution system. For example, if implemented by hardware, as in another embodiment, it can be implemented by any one of the following technologies known in the art or their combination: a discrete logic circuit having a logic gate circuit for implementing a logic function for a data signal, a dedicated integrated circuit having a suitable combination of logic gate circuits, a programmable gate array, a field programmable gate array, etc.

[0144] A person skilled in the art may understand that all or part of the steps in the method for implementing the above-mentioned embodiment may be completed by instructing related hardware through a program, and the program may be stored in a computer-readable storage medium, which, when executed, includes one or a combination of the steps of the method embodiment.

[0145] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for regulating a composite material, characterized in that: The following steps are involved: Obtaining the compressive strength and fracture toughness of the initial composite material, and the compressive strength and fracture toughness of the target composite material; Determining a filler, a filling particle size of the filler, a replacement material, and a replacement ratio of the replacement material according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material; The target composite material is prepared according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material.

2. The method according to claim 1, characterized in that The step of determining the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material comprises: If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a first preset threshold, and the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is greater than a second preset threshold, at least one fine particle inert material is determined as a filler, at least one of a cementitious material, water and a coarse particle material in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a first ratio; If the absolute value of the difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is less than a third preset threshold, and the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fourth preset threshold, wherein the fourth preset threshold is greater than the third preset threshold, then at least one fine particle inert material and / or at least one active material is determined as a filler, at least one of a cementitious material, water and coarse particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a second ratio; If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fifth preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a sixth preset threshold, wherein the fifth preset threshold is greater than the sixth preset threshold, then at least one fine particle inert material and / or at least one active material is determined as a filler, at least one of water and coarse particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a third ratio; If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a seventh preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than an eighth preset threshold, wherein the eighth preset threshold is greater than the seventh preset threshold, then at least one coarse particle inert material and / or at least one active material is determined as a filler, at least one of a cementitious material, water and fine particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a fourth ratio; If the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a ninth preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a tenth preset threshold, at least one active material is determined as a filler, at least one of the gelling material, water and fine particles in the initial composite material is determined as a replacement material, and the replacement ratio of the replacement material is determined to be a fifth ratio.

3. The method according to claim 2, characterized in that The cementitious material is at least one of ordinary silicate cement, sulphoaluminate cement, aluminate cement, magnesium-based cement, carbonate cementitious material, alkali-activated cementitious material and building gypsum.

4. The method according to claim 1, characterized in that Before obtaining the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material, the method comprises: Obtain target compressive strength; Determining a basic ratio of the initial composite material according to the target compressive strength, and preparing the initial composite material based on the basic ratio; The initial composite material is tested to obtain the fracture toughness and actual apparent packing density of the initial composite material, and the particle packing density and particle gap volume of the initial composite material are determined using a preset calculation model.

5. The method according to claim 1, characterized in that After the target composite material is prepared according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material, the method further includes: Testing the target composite material to obtain actual compressive strength and actual fracture toughness of the target composite material; Determining whether the actual compressive strength is within a preset strength range, and whether the actual fracture toughness is within a preset toughness range; If the actual compressive strength is not within the preset strength range, or the actual compressive strength is not within the preset toughness range, the optimized ratio of the target composite material is determined based on the compressive strength and fracture toughness of the target composite material and the actual compressive strength and actual fracture toughness of the target composite material, and the optimized target composite material is prepared based on the optimized ratio.

6. A control device for composite materials, characterized in that: include: An acquisition module, used for acquiring the compressive strength and fracture toughness of the initial composite material, and the compressive strength and fracture toughness of the target composite material; A determination module, configured to determine a filler, a filling particle size of the filler, a replacement material, and a replacement ratio of the replacement material according to the compressive strength and fracture toughness of the initial composite material and the compressive strength and fracture toughness of the target composite material; A preparation module is used to prepare the target composite material according to the filler, the filling particle size of the filler, the replacement material and the replacement ratio of the replacement material.

7. The device according to claim 6, characterized in that The determining module comprises: a first determining unit, configured to determine at least one fine-grained inert material as a filler, determine at least one of a cementitious material, water and a coarse-grained material in the initial composite material as a replacement material, and determine a replacement ratio of the replacement material to be a first ratio when a difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a first preset threshold value, and a difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is greater than a second preset threshold value; a second determining unit, for determining, when an absolute value of a difference between the fracture toughness of the initial composite material and the fracture toughness of the target composite material is less than a third preset threshold value, and a difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fourth preset threshold value, wherein the fourth preset threshold value is greater than the third preset threshold value, to determine at least one fine particle inert material and / or at least one active material as a filler, to determine at least one of a cementitious material, water and coarse particles in the initial composite material as a replacement material, and to determine a replacement ratio of the replacement material to be a second ratio; a third determining unit, for determining, when a difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a fifth preset threshold, and a difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a sixth preset threshold, wherein the fifth preset threshold is greater than the sixth preset threshold, at least one fine particle inert material and / or at least one active material as a filler, at least one of water and coarse particles in the initial composite material as a replacement material, and a replacement ratio of the replacement material to be a third ratio; a fourth determining unit, for determining, when the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a seventh preset threshold, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than an eighth preset threshold, wherein the eighth preset threshold is greater than the seventh preset threshold, at least one coarse particle inert material and / or at least one active material as a filler, determining at least one of a cementitious material, water and fine particles in the initial composite material as a replacement material, and determining the replacement ratio of the replacement material to be a fourth ratio; a fifth determination unit, for determining at least one active material as a filler, determining at least one of the cementitious material, water and fine particles in the initial composite material as a replacement material, and determining the replacement ratio of the replacement material to be a fifth ratio when the difference between the compressive strength of the target composite material and the compressive strength of the initial composite material is greater than a ninth preset threshold value, and the difference between the fracture toughness of the target composite material and the fracture toughness of the initial composite material is greater than a tenth preset threshold value.

8. The device according to claim 7, characterized in that The cementitious material is at least one of ordinary silicate cement, sulphoaluminate cement, aluminate cement, magnesium-based cement, carbonate cementitious material, alkali-activated cementitious material and building gypsum.

9. An electronic device, characterized in that: include: A memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor executes the program to implement the method for controlling the composite material according to any one of claims 1 to 5.

10. A computer-readable storage medium having a computer program stored thereon, characterized in that: The program is executed by a processor to implement the control method of the composite material as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Ordered heterostructure multi-metal composite material and preparation method thereof

    CN117340274A

  • Multifunctional nanocomposite reinforced with impregnated honeycomb carbon nanostructures

    CN117551333A

  • Cements reinforced with graphene nanoplatelets or helical carbon nanotubes

    US20220242787A1